1997
DOI: 10.1111/j.1469-7793.1997.321bk.x
|View full text |Cite
|
Sign up to set email alerts
|

Receptors couple to L‐type calcium channels via distinct Go proteins in rat neuroendocrine cell lines

Abstract: The present study examines the hypothesis of G protein subtype selectivity in receptor‐induced inhibition of calcium channel currents (ICa) in the insulin‐secreting RINm5F and pituitary GH3 rat cell lines. Specificity of receptor coupling to G proteins was studied by infusion of purified Ga isoforms into cells via a patch pipette. In RINm5F cells, the neuropeptide galanin inhibited dihydropyridine (DHP)‐ and ω‐conotoxin‐sensitive components of ICa and slowed down their activation kinetics. In GH3 cells, DHP‐se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“…Activation of the K ATP channel, which hyperpolarizes the cell membrane, prevents insulin secretion from pancreatic islets, and modulation of the channel activity has been a therapeutic for treating type II diabetes. G o2 can also mediate somatostatin-induced inhibition of Ca 2+ currents in the GH3 rat neuroendocrine cell line (46). Intracellular calcium is a central regulator for triggering the secretory machinery.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of the K ATP channel, which hyperpolarizes the cell membrane, prevents insulin secretion from pancreatic islets, and modulation of the channel activity has been a therapeutic for treating type II diabetes. G o2 can also mediate somatostatin-induced inhibition of Ca 2+ currents in the GH3 rat neuroendocrine cell line (46). Intracellular calcium is a central regulator for triggering the secretory machinery.…”
Section: Resultsmentioning
confidence: 99%
“…Purified ␤␥-subunits and ␣ i /␣ o -subunits from brain were kindly donated by Dr. G. Schultz (Institut fü r Pharmakologie, Freie Universität, Berlin, Germany) (9). The GST fusion protein containing a carboxylterminal fragment (residues 546 -670) of ␤-adrenergic receptor kinase-1 (␤ARK1-CT/GST) and the corresponding GST protein were a gift of Dr. R. J. Lefkowitz (Howard Hughes Medical Institute, Duke University Medical Center, Durham, NC) (10).…”
Section: Methodsmentioning
confidence: 99%
“…The activation is terminated by a GTPase activity intrinsic to the α-subunit. It is also widely accepted that G o α is primarily responsible for the modulation of neuronal voltage-dependent Ca 2+ channels [4,7,8,28], although several Gβγ subunits are able to transduce the signal to Ca 2+ channels [14,17]. We found that hypoxia induced an average decrease of about 25% in the levels of G i/o immunoreactivity.…”
Section: Discussionmentioning
confidence: 52%
“…Indeed, it is already established that membrane-delimited G protein regulation of Ca 2+ channels is common in neurons and that the G protein involved in this inhibition is PTX sensitive [7,12,16,36]. Growing evidence strongly implicates G o rather than G i in this regulation, which could also affect the suppression of neurotransmitter release that is mediated by receptors on presynaptic neurons [4,7,8,28]. Furthermore, membrane-delimited G protein regulation of I Ca by DA has been shown in chick sensory and sympathetic neurons [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation